BloodNetwork: blood donors community mobile application / Muhammad Ashraf Umar - Umar, Muhammad Ashraf (2021)
Blood had always been on demand all over the world. Blood donation would sometimes appear as troublesome to some people due to busy working schedule and the difficulty to search for nearest location and nearest blood donation events. The lack of advertising element in an event may resulted to low numbers of blood donors. The objectives of this project are to identify the user requirements for BloodNetwork application, to design and develop BloodNetwork application by following the Mobile Application Development Life Cycle (MADLC) methodology. This project however will be developing up until testing phase only. This project is intended to create blood donor’s community platform whereby the donors can locate blood donation events even in busy working list and creating awareness on the importance of blood donation while ensuring the repeating blood donation among blood donors. Geolocation technology will help users to stay informed of the location of blood donation events. Users may chat with other blood donors in requesting for blood and asking for advices for the potential blood donors. BloodNetwork can set a reminder for blood donors on their future donation in their device’s calendar application. The public user and the healthcare industry are the significance for this project. Users does not need to search for blood donation events in social media anymore hence it is time consuming and the blood supply may slightly increase due to the awareness on the importance of blood donation. For the future direction of BloodNetwork, this project is planning to be collaborating with National Blood Centre Malaysia to know the blood donation records for the blood donors and the insufficient blood supply in other regions. However, the limitation of this application is the chatting feature can only be used if the user’s device is installed with WhatsApp application.